2017
DOI: 10.1371/journal.pone.0176037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on composition changes of selected spices

Abstract: The present investigation was conducted to study the true retentions of α-tocopherol, tocotrienols and β-carotene in crown daisy, unripe hot pepper, onion, garlic, and red pepper as affected by various domestic cooking methods, those were, boiling, baking, stir-frying, deep-frying, steaming, roasting, and microwaving. Fatty acid compositions were determined by GC, and HPLC were used for quantification of α-tocopherol, tocotrienols, and β-carotene. True retentions of α-tocopherol in cooked foods were as follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…Both Nixon and Brian ( 2020 ) discovered a 13.5% loss of TCC in hot peppers during boiling, which was in contrast to the 0.33 percent loss in ESS. Contrarily, according to a number of researchers (Cai‐Hua et al., 2017 ; Hwang et al., 2012 ; Nixon and Brian, 2020 ), home cooking enhanced TCC in comparison to uncooked samples. This was in accordance with the percent raise in CSS (0.47).…”
Section: Resultsmentioning
confidence: 99%
“…Both Nixon and Brian ( 2020 ) discovered a 13.5% loss of TCC in hot peppers during boiling, which was in contrast to the 0.33 percent loss in ESS. Contrarily, according to a number of researchers (Cai‐Hua et al., 2017 ; Hwang et al., 2012 ; Nixon and Brian, 2020 ), home cooking enhanced TCC in comparison to uncooked samples. This was in accordance with the percent raise in CSS (0.47).…”
Section: Resultsmentioning
confidence: 99%
“…Weil et al (2017) used wild Piper Borbonense pepper for blanching and drying treatments; they found that these operations produced minor changes in essential oil composition but major modifications in pepper color. Jia et al (2017) investigated the retention of αtocopherol, tocotrienols, and β-carotene in unripe hot and red pepper samples after domestic cooking methods, like boiling, baking, stir-frying, deep-frying, steaming, roasting, and microwaving. Surprisingly, all cooking methods in all peppers produced high retention of α-tocopherol and α-tocotrienol; but deep-frying showed the highest values.…”
Section: Effects Of Processing On the Preservation Of Pepper And On Imentioning
confidence: 99%
“…In the last few years, interest in the bioactive compounds from chili ( i.e ., capsaicinoids, carotenoids, polyphenols, flavonoids, vitamins, proteins, fibers, oils, and minerals) has increased in view of their health benefits as antioxidants, anti‐inflammatory, hypolipidemic, hypoglycemic, and analgesic effects. Different types of chili fruits may be produced along the year but their fresh state is not long and high losses may take place from the production areas to the consumption centers; storage and transportation negative effects have made necessary to improve their preservation (Jia, Shin, Kim, & Lee, 2017; Sanatombi & Rajkumari, 2020).…”
Section: Effects Of Processing On the Preservation Of Pepper And On Imentioning
confidence: 99%
See 1 more Smart Citation
“…(Sánchez-Segura et al 2015). Interest in the phytochemical compounds found in peppers has grown due to their antioxidant, anti-in ammatory, hypolipidemic, hypoglycemic, and health-promoting properties(Jia et al 2017). Phenolic compounds can neutralize free radicals in vitro and in vivo, which are implicated in conditions like cancer, aging, and certain neurodegenerative diseases(Bogusz et al 2018).…”
mentioning
confidence: 99%